How Self-regulated Learning and Motivation Affect Mathematics Outcomes of Students Living in Boarding Schools and at Home - Widyaningrum, Anggita Cahya; Fadhila, Yoan Afra; Dewanti, Sintha Sih (Jurnal Tadris Matematika, 2024)
This study aims to analyze the effects of self-regulated learning and learning motivation on mathematics learning outcomes among students residing in boarding schools and at home. The study used a quantitative approach with a survey method. The sample consisted of 90 students of Madrasah Aliyah in Yogyakarta, which was taken using a purposive sampling technique, with 45 students living in boarding schools and 45 students living at home. The research instruments included questionnaires to measure self-regulated learning and learning motivation, as well as midterm assessment test results to evaluate mathematics learning outcomes. The data were analyzed using multiple linear regression. The results showed that self-regulated learning and learning motivation had an influence of 7.9% on the learning outcomes of students living in boarding schools and 8.5% on students living at home. Learners at home exhibited a stronger positive relationship between learning motivation and learning outcomes compared to learners in boarding schools. Learning motivation, especially intrinsic ones, is an important factor in supporting learners' learning outcomes at home, while the structured environment in boarding schools tends to make other factors, such as teaching methods and facilities, more dominant.